2014
DOI: 10.1186/1746-6148-10-79
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endogamy and mitochondrial DNA on immunological parameters in cattle

Abstract: BackgroundEndogamy increases the risk of manifestation of deleterious recessive genes. Mitochondrial DNA allows the separation of American Zebu (Bos indicus and Bos taurus) and evaluate the effect of mitochondrial DNA on productive traits of cattle. However, the effect of endogamy and mitochondrial DNA (mtDNA) on the immune system remains unclear. The aim of this study was to evaluate the association between endogamy, mtDNA and immune parameters.ResultsA total of 86 cattle (43 cows and 43 calves) were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In cattle, inbreeding has been also associated with changes in the immune system [ 74 ] and an increased occurrence of respiratory diseases [ 75 ]. Our results also identified a metabolic pathway related to B-defensin genes.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, inbreeding has been also associated with changes in the immune system [ 74 ] and an increased occurrence of respiratory diseases [ 75 ]. Our results also identified a metabolic pathway related to B-defensin genes.…”
Section: Discussionmentioning
confidence: 99%
“…TLR5 is located extracellularly and recognizes flagellin, which is a structural component of the flagellum in flagellated bacteria (Hayashi et al, 2001;Smith et al, 2003), whereas TLR9 is located intracellularly and recognizes unmethylated CpG dinucleotides that are found in Gram-positive and Gramnegative bacteria (Griebel et al, 2005;Dalpke et al, 2006). Previous reports indicated that genotypic and phenotypic factors modulate the uterine defense mechanisms in cows (Horne et al, 2008;Sordillo et al, 2009), and a study verified that endogamy also interfere with immune parameters of Zebu cattle (Macêdo et al, 2014). Hypothetically, decreased transcription of TLR5 could increase susceptibility to flagellated bacteria in Gyr cows at 7 days post partum, whereas increased transcription of TLR9 could be associated with resistance against bacteria located intracellularly in the endosomal compartment (Janeway and Medzhitov, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…In cattle, artificial reproduction technologies allow the reduction in the number of animals needed to produce the next generation and the reduction in generation intervals. Consequently, the increase in the relatedness levels in the population is usually a result of the selection process (Macedo et al., ; Panetto, Gutiérrez, Ferraz, Cunha, & Golden, ). Samples may capture such phenomena and association studies, and may be affected by the population genetic structure.…”
Section: Discussionmentioning
confidence: 99%